Faculty's conceptions of teaching introductory economics in higher education: A phenomenographic study in a South African context. (January 2019) - Ojo, Emmanuel; Booth, Shirley; Woollacott, Laurie
Abstract: In view of the on-going global debate about the economics curriculum and its teaching, this paper explores how the faculty responsible for teaching introductory economics at a South African university understand learning and teaching of their subject. We have adopted a qualitative research approach, phenomenography, to complement what we already know from mainstream literature on undergraduate economics education, predominantly published by academic economists using a quantitative methodology. After a phenomenographic analysis of interview data with lecturers and tutors, six conceptions of teaching introductory economics ( Economics 1 ) emerged: (I) team collaboration to implement the economics curriculum; (II) a thorough knowledge of the content; (III) implementing the curriculum in order for students to pass assessment; (IV) helping students learn key economics concepts and representations to facilitate learning; (V) engaging students through their real-life economics context to acquire economic knowledge; and (VI) helping students think like economists. These are discussed first in relation to the implications for student learning and second, in a broader context of higher education discourses and educational development.